The Role of Educators in Facing the High Accessibility of Students on Social Media - Hardiyanti, Retno Ayu; Azzam, Fajar Abdullah (Universitas Pendidikan Indonesia (UPI), 2022)
This article has a background of changing communication patterns in the midst of massive digital developments. This is a challenge for educators in interacting with students, including lecturers dealing with their students in order to adapt to the times. Specifically, this research was conducted on students of Social Studies Education, Universitas Pendidikan Indonesia. Through the survey method conducted in this study, it shows that students are very active in accessing social media. However, they are not active enough to participate when using social media. This is a new challenge for educators in the field of social studies education to be able to involve a number of approaches or use popular applications in the learning process. This study intends to present an idea that the tendency of students in the digital era must be balanced with the competence of educators to collaborate with technology and be accompanied by things that are liked by students.